« Traistre parjure ! » Serment, contrat et alliance chez les Monarchomaques - Paul-Alexis Mellet (Etudes Epistémè)
The purpose of this article is to explore the role of oaths during the French civil wars, especially among those called the calvinist Monarchomachs, so as to better understand the XVIth-century political French institutions and to assess the extent to which the Monarchomachs compared them with the Polish, Aragonese and English institutions, in order to define the conditions of obedience to the king, as opposed to a prince sharing his power with a representative institution. More specifically, we shall try and define what an oath is, and what its function is in the Monarchomachs’ thinking. What words are used to designate it? What models most inspired those thinkers? What authors or institutional models helped them elaborate their own theories? By distinguishing between the terms “oath”, “covenant” and “contract” and by taking their inspiration from classical (ephors in Sparta, Roman Senate, etc.) or contemporary (Germany, Aragon, etc.) models, the Monarchomachs eventually determined the conditions in which a tyrant may be lawfully resisted: only the magistrates can act, without going further than deposing him.